(untitled) (Indian Journal of Animal Production and Management, 2026)
Background: Fasciolosis is a prevalent parasitic diseasethat affects mammals worldwide. This disease is associated with global veterinary and economic importance in the livestock breeding and production systems, particularly cattle. In infected animals, fasciolosis may induce significant disturbances in the hematological profile and oxidative stress biomarkers. Aim: This study aimed to evaluate selected oxidative stress biomarkers (by using bovine-specific ELISA kits in place of the traditional methods) and hematological changes in calves naturally infected with fasciolosis and to assess their possible role as supportive diagnostic indicators of the disease. Methods: This study involved a total of 89 male calves (20–24 months old). The animals included in this study were randomly selected from those presented for slaughter throughout the study period. Post-mortem macroscopic examination of the liver and bile ducts, along with microscopic identification of trematodes based on morphological features, was used to confirm infection. Blood samples were collected, and serum was separated for biochemical analysis. Oxidative stress biomarkers were assessed using bovine-specific ELISA kits, and hematological parameters were measured using an automated complete blood count (CBC) analyzer. Results: Infected calves showed a highly significant reduction in antioxidant parameters compared with controls. Mean serum SOD, CAT, and GSH levels in infected animals (574.88 ± 26.71 pg/mL, 0.96 ± 0.13 ng/ mL, and 6.97 ± 0.58 ng/mL, respectively) were significantly lower in infected animals versus controls (940.80 ± 42.94 pg/mL, 3.43 ± 0.38 ng/mL, 18.54 ± 0.24 ng/mL, respectively). Conversely, MDA levels (155.99 ± 15.09 ng/mL) were markedly elevated in the infected group compared to controls (55.78 ± 3.76 ng/ mL).The hematological analysis revealed significant alterations in the infected group compared to the control group. The mean RBC count in infected animals (7.45 ± 0.51 × 10¹²/L) was significantly lower than that in the control group (10.0 ± 0.55 × 10¹²/L). Similarly, hemoglobin (HGB) levels were markedly decreased in infected animals (8.80 ± 0.92 g/dL) versus controls (14.0 ± 0.72 g/dL). Hematocrit (HCT) values also showed a significant reduction in infected animals (26.6 ± 3.0%) compared to controls (42.1 ± 2.2%). In addition, mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) were significantly lower in the infected group (35.7 ± 3.4 fL and 11.8 ± 1.5 pg, respectively) than in the control group (42.1 ± 3.1 fL and 14.0 ± 1.1 pg, respectively).In contrast, no significant difference was observed in mean corpuscular hemoglobin concentration (MCHC) between the infected (33.0 ± 1.9 g/dL) and control groups (33.2 ± 1.4 g/dL). Conclusion: Fasciolosis has a notable impact on both biochemical and hematological profiles in calves; such clinicopathological alterations may serve as valuable supportive markers for determining the physiological consequences of infection and may aid in early diagnosis, assessment of disease severity, and monitoring the progression of infection. Additional research is needed to determine the effect of preventing or promptly correcting these alterations in accelerating recovery and improving the overall health condition of affected animals.